Milton Friedman's monetary framework : a debate with his critics - Friedman, Milton; Gordon, Robert J.; Friedman, Milton (Chicago : University of Chicago Press, 1974)
This volume presents a debate between Milton Friedman and five top monetary theorists. The discussion centers on a combined version of Friedman's "A theoretical Framework for Monetary Analysis" and "A Monetary Theory of Nominal Income," which originally appeared in the Journal of Political Economy. The evaluations of Friedman's controversial theories and Friedman's reply to his critics are important contributions to an understanding of current monetary theory.
Includes index.
Bibliography: p. 178-185.
usc 12/02/2018
Loans
Keywords: Friedman, Milton; Quantity theory of money; Money